DETECTION AND IDENTIFICATION OF SLIDING PLANES USING GEOELECTRIC METHODS AT BENGKAUNG TOURISM AREA, LOMBOK ISLAND - Pratama, Muhammad Andika; Minardi, Suhayat; Marzuki, Marzuki (Indonesian Physical Review, 2024)
Landslides are among the most common problems on natural and man-made slopes. Factors that cause landslides are the presence of a sliding plane, steep slope, and the type of rock, while the triggers of landslides are vibration, human activity, and water infiltration into the slope. The sliding plane itself is an impermeable and slippery plane that is usually in the form of a clay layer so that it becomes the foundation for the movement of soil masses. This study aims to determine the type of rock and the depth of the potential landslide slide plane in Bengkaung Village. The data used in this study is data obtained by taking direct measurements in the field, namely by injecting electric current into the earth using geoelectric method tools. Data processing, namely by using the Res2dinv application. The results of this study are the types of rocks in the study area in the form of sandstone, clay, silt, limestone, breccia, and lava, and the depth of the sliding plane is between 2.8-5 meters